Perbandingan Biaya dan Waktu Pelaksanaan Deck on Pile dengan Cakar Ayam Modifikasi pada Pembangunan Dermaga Jakarta International Container Terminal 2 - Yulianto, Yulianto; Azhar, Moh.; Naibaho, Pio Ranap Tua; Sembiring, Kristina (Universitas Ibn Khaldun, 2026)
Indonesia as a maritime country is required to be able to follow the development of the international world to become the world's maritime axis, by developing medium and large ports and encouraging investment in the maritime sector on a large scale. Trisakti Terminal, Tanjung Priok branch, North Jakarta is a busy terminal among ten other terminals managed by PT. Pelabuhan Indonesia I (Persero) which serves general cargo and dry bulk types both domestically and internationally. This study aims to compare the efficiency values ​​obtained from the application of deck on slab foundations with modified spread footing foundation (Cakar Ayam Modifikasi). In the construction work of modified spread footing foundation, the cost of the work is Rp51,099,780,000, with an implementation time of 240 calendar days, while in the construction of Deck on Pile the total cost of the work is Rp88,160,700,000, with an implementation time of 240 calendar days, strict supervision is needed after concrete piling because the remaining implementation time is 14 weeks. The cost efficiency of the modified spread footing foundation work on Deck on Pile is 40%, while the time efficiency of the modified spread footing foundation work on Deck on Pile is 11%.